(untitled) (Journal of Educational Sciences, 2020)
In this article the authors define the quality of education in the most prestigious universities in the world. The main goal is to bring the quality of universities in the country as far as possible to this level defining various criteria of competitiveness between world universities. The following requirements for any university by the standards of higher education institutions show how important and necessary sci- ence is for modern society. Therefore, the country’s education sector determines its place in the world from scientific achievements, based on these criteria. Comparing the results of several rankings through Internet sources, the quality and level of educa- tion of universities in Kazakhstan were assessed. As a result, the quality and level of education of higher educational institutions of Kazakhstan among the universities of the world were determined, and also one has to work for the professors and teaching staff of universities in order to be among the best accord- ing to various criteria of world famous universities. The authors emphasize that today Kazakhstan ranks second after Russia in terms of the level of development of universities in the field of education and its integration into the global educational space (according to the analysis of ratings). Ideas from the authors will also be proposed to solve the problem. Key words: rating, education, quality, university, teacher.